Dark Waves: The Synthesizer and the Dystopian Sound of Britain (1977-80) - O'Connor, Neil (Rowman & Littlefield Publishers, 2023)
Between 1977 and 1980, Britain was a country and culture in flux. The threat of nuclear war, mass unemployment, and strikes made it a particularly gloomy period historically. Within this, a growing number of electronic music acts were using technology and the synthesizer to soundtrack changing times. Dark Waves: The Synthesizer and the Dystopian Sound of Britain (1977- 80) is the first musicological collection of essays on acts that include Throbbing Gristle, Cabaret Voltaire, and The Human League, mapping how the synthesizer spurred toward a fundamental shift in the mechanisms of electronic musicmaking in late 1970s. The volume traces how, along with the musical aesthetics established by both the Punk and Post-Punk movements, the synthesizer led to new and innovative effects, ideas, processes, and musical genres. Dark Waves explores the background, influences, and use of technology and how such developments would result in the more commercial electronically produced sound of 1980s synth pop which, in turn, shaped the sound of electronic music today.